An Exploration of the Counselling Experiences of Women who Work in the Indoor Sex Industry - Velez, Camila (Université d'Ottawa / University of Ottawa, 2017)
The purpose of this qualitative study is to enrich the understanding of the counselling and psychotherapy experiences of women who have previously or currently worked in the Canadian sex industry. I conducted semi-structured interviews with 6 participants ranging in age from 19 to 52 who described an individual counselling experience in which they revealed their sex work employment status. I analyzed the interview drawing from a Gadamerian hermeneutic phenomenological approach grounded in feminist standpoint theory. The results revealed 17 themes organized in 5 categories: (a) seeking counselling, (b) the therapeutic relationship, (c) disclosure of sex work, (d) counselling outcomes, and (e) recommendations for counsellors working with sex workers. The results shed light on indoor sex worker clients’ heterogeneous counselling needs, expectations, and experiences, providing valuable considerations for culturally responsive and socially just practice with sex workers. The discussion of the results reflects previous research studies, clinical implications, and suggestions for future research.
Keywords: sex work; sex industry; counselling; psychotherapy; Feminist standpoint theory; hermeneutic phenomenology; qualitative study; indoor sex work